Aspectos legales de la tecnología Blockchain - Morales Cáceres, Alejandro Rafael (2023)
The Blockchain has emerged in recent years as a technology that promises to revolutionize the way transactions are carried out globally, in this sense, through this article the author provides an approach about what the Blockchain is, how it is a means that has facilitated the rise of cryptocurrencies —which do not require an intermediary bank to make payments over the internet—, the advent of smart contracts that operate automatically to regulate business carried out through virtual means, going through explaining what is the tokenization of assets —tangible or intangible— for their subsequent commercialization using the Blockchain, as well as reflecting on the incorporation of these innovations into the national legal system.